Reliability, Validity, and Gender Invariance of the Exercise Benefits/Barriers Scale: An Emerging Evidence for a More Concise Research Tool - Koehn, Stefan (Int J Environ Res Public Health, 2021)
The Exercise Benefits/Barriers Scale (EBBS) research instrument has been extensively used to investigate the perceived benefits and barriers of exercise in a range of settings. In order to examine theoretical contentions and translate the findings, it is imperative to implement measurement tools that operationalize the constructs in an accurate and reliable way. The original validation of the EBBS proposed a nine-factor structure for the research tool, examined the EBBS factor structure, and suggested that various factors are important for the testing of the perception of exercise benefits and barriers, whereas a few items and factors may not be vital. The current study conducted a confirmatory factor analysis (CFA) using hierarchical testing in 565 participants from the northwest region of the United Kingdom, the results of which provided evidence for a four-factor structure of the benefits measure, with the Comparative Fit Index (CFI) = 0.943, Tucker–Lewis Index (TLI) = 0.933, and root means square error of approximation (RMSEA) = 0.051, namely life enhancement, physical performance, psychological outlook, and social interaction, as well as a two-factor structure of the barrier measures, with the CFI = 0.953, TLI = 0.931, and RMSEA = 0.063, including exercise milieu and time expenditure. Our findings showed that for a six-factor correlated model, the CFI = 0.930, TLI = 0.919, and RMSEA = 0.046. The multi-group CFA provided support for gender invariance. The results indicated that after three decades of the original validation of the EBBS, many of the core factors and items are still relevant for the assessment of higher-order factors; however, the 26-item concise tool proposed in the current study displays a better parsimony in comparison with the original 43-item questionnaire. Overall, the current study provides support for a reliable, cross-culturally valid EBBS within the UK adult population, however, it proposes a shorter and more concise version compared with the original tool, and gives direction for future research to focus on the content validity for assessing the perception of the barriers to physical activity.